2019
DOI: 10.3390/md17100589
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Properties of Gelatin Extracted from Marine Snail Rapana venosa

Abstract: In this study, we aimed to obtain gelatin from the marine snail Rapana venosa using acidic and enzymatic extraction methods and to characterize these natural products for cosmetic and pharmaceutical applications. Marine gelatins presented protein values and hydroxyproline content similar to those of commercial mammalian gelatin, but with higher melting temperatures. Their electrophoretic profile and Fourier transform infrared (FTIR) spectra revealed protein and absorption bands situated in the amide region, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…Marine gelatins possess high protein values (91.5% for acid-soluble gelatin and 83.1% for pepsin-soluble gelatin). The hydroxyproline content of marine gelatin is similar to that of commercial mammalian gelatin but with higher melting temperatures [ 144 ]. Some marine gelatin such as those derived from saithe ( Pollachius virens ) skin has a considerable mineral content (>20%) compared to the commercially available gelatin (<0.2%) [ 145 ].…”
Section: Biomaterials From Marine Organismsmentioning
confidence: 99%
“…Marine gelatins possess high protein values (91.5% for acid-soluble gelatin and 83.1% for pepsin-soluble gelatin). The hydroxyproline content of marine gelatin is similar to that of commercial mammalian gelatin but with higher melting temperatures [ 144 ]. Some marine gelatin such as those derived from saithe ( Pollachius virens ) skin has a considerable mineral content (>20%) compared to the commercially available gelatin (<0.2%) [ 145 ].…”
Section: Biomaterials From Marine Organismsmentioning
confidence: 99%
“…Gelatin (Table 9) can serve as cell carrier to repair tissue defects, i.e., gelatin extracted from marine snail Rapana venosa was reported as a biocompatible template for the growth of human keratinocytes [289]. Hence, this marine biomaterial can be used in tissue engineering, often in combination with other materials such as chitosan and silk fibroin [42].…”
Section: Gelatinmentioning
confidence: 99%
“…When linked between gelatin microstructure with protein quality and yield, it can be concluded that high yield will produce a high protein and have better microstructure quality. The quality of gelatin morphology is closely related to the quality of viscosity (Nuamsrinuan et al, 2015) The quality of gelatin morphology is also influenced by cross-linking that occurs in gelatin (Gaspar-Pintiliescu et al, 2019).…”
Section: Protein Contentmentioning
confidence: 99%